(untitled) (Biological Sciences - PJSIR, 1998)
Experimental and theoretical studies of subsynchronous resonance phenomena are carried out on a power system com- posed of a small rating motor-generator set connected to an infinite bus by a series capacitor-compensated transmission line. Complete representation of the electromechanical system is adopted. The eigenvalue method of analysis is used to study the interaction between mechanical and electrical network dynamic behaviour to identify the various conditions under which the system wouldbe subjected totorsional interaction.The impactof subsynchronous resonance on dynamic stability is also explored.